2015
DOI: 10.1123/japa.2013-0223
|View full text |Cite
|
Sign up to set email alerts
|

Counting Steps in Institutionalized Older Adults During Daily Life Activities: The Validation of Two Motion Sensors

Abstract: The primary purpose of this study was to assess the validity of two motion sensors in measuring steps in institutionalized older adults during daily life activities. Sixty-eight nursing home residents (85.8 ± 5.6 years) were equipped with a hip-worn and ankle-worn piezoelectric pedometer (New Lifestyles 2000) and with an arm-mounted multisensor (SenseWear Mini). An investigator with a hand counter tallied the actual steps. The results revealed that the multisensor and hip- and ankle-worn pedometer significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…These five studies included one validation study and four interventions studies in older adults, of which only the pretest data were included in these analyses (Martien, Delecluse, Seghers, & Boen, 2014;Pelssers et al, 2013;Van Hoecke, Delecluse, Bogaerts, & Boen, 2013;Van Roie, Delecluse, Coudyzer, Boonen, & Bautmans, 2013). Participants gave written informed consent and all procedures were approved by the human Ethics Committee of KU Leuven.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…These five studies included one validation study and four interventions studies in older adults, of which only the pretest data were included in these analyses (Martien, Delecluse, Seghers, & Boen, 2014;Pelssers et al, 2013;Van Hoecke, Delecluse, Bogaerts, & Boen, 2013;Van Roie, Delecluse, Coudyzer, Boonen, & Bautmans, 2013). Participants gave written informed consent and all procedures were approved by the human Ethics Committee of KU Leuven.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Efforts have been made to ensure that the developed method is as relevant as possible for step count in patients with LSS, including a well-described and broad-ranged patient population representing both surgical and nonsurgical candidates. 56 It is, however, still applicable only to patients from secondary care, and patients were not invited consecutively, but according to age and walking capacity to challenge the method in areas previously seen as difficult concerning step count; 37,39,43,44 thus the method could provide skewed results in a representative LSS population.…”
Section: Discussionmentioning
confidence: 99%
“…32 The accuracy of step count by wearable sensors has been evaluated among age-matched healthy individuals. [33][34][35][36][37][38] It has been shown that the use of walking aids 33,34,36,[39][40][41][42] and slow walking speed 37,39,43,44 may impede step detection. The literature points to devices placed distally on lower extremities as more robust at detecting steps.…”
mentioning
confidence: 99%
See 2 more Smart Citations